2019
DOI: 10.1007/s10750-019-3933-8
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent impacts of allelopathy on growth, pigment, and lipid content between a subpolar strain of Synechocystis sp. CCBA MA-01 and coexisting microalgae

Abstract: Picocyanobacteria represent the main fraction of ocean primary production and, due to the effects of ocean acidification and an increase in seawater temperature, this group is expected to be favored in future scenarios. For this reason, we studied the ecophysiological response of picocyanobacteria to increases in water temperature by testing the allelopathic activity of a subpolar strain of Synechocystis sp., grown at a temperature range of 10-20°C, against coexisting microalgae. We showed that cell-free filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Compounds produced by dominant phytoplankton groups in coastal and open-ocean areas (e.g., PUAs by diatoms, microcystins-like compounds by Synechococcus ) have been shown to inhibit microzooplankton growth in natural communities ( Lavrentyev et al, 2015 ; Sliwinska-Wilczewska et al, 2017 ). These allelopathic effects can be enhanced by warming ( Felpeto et al, 2019 ) and nutrient-limited conditions ( Fistarol et al, 2005 ). Also, warmer environments and/or low (or limiting) nutrient availability can lead to increased phytoplankton carbon:nutrient stoichiometry, i.e., seston with reduced nutritional quality ( De Senerpont Domis et al, 2014 ), which constitutes an effective defense mechanism against herbivore predators ( Branco et al, 2020 ), and could help explain inverse relationship between temperature and grazing pressure found in temperate, tropical open-ocean and polar coastal ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds produced by dominant phytoplankton groups in coastal and open-ocean areas (e.g., PUAs by diatoms, microcystins-like compounds by Synechococcus ) have been shown to inhibit microzooplankton growth in natural communities ( Lavrentyev et al, 2015 ; Sliwinska-Wilczewska et al, 2017 ). These allelopathic effects can be enhanced by warming ( Felpeto et al, 2019 ) and nutrient-limited conditions ( Fistarol et al, 2005 ). Also, warmer environments and/or low (or limiting) nutrient availability can lead to increased phytoplankton carbon:nutrient stoichiometry, i.e., seston with reduced nutritional quality ( De Senerpont Domis et al, 2014 ), which constitutes an effective defense mechanism against herbivore predators ( Branco et al, 2020 ), and could help explain inverse relationship between temperature and grazing pressure found in temperate, tropical open-ocean and polar coastal ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been also made for other picocyanobacterium Synechocystis sp. [28]. Contrary to that, Synechococcus sp.…”
Section: Discussionmentioning
confidence: 73%
“…The allelopathic activity between marine Synechococcus strains CC9605, CC9311, and WH8102 has also been showed by Paz-Yepes et al [27]. There are also reports of allelopathic activity of marine picocyanobacteria of the genus Synechocystis CCBA MA-01 [28]. In these studies, it was shown that picocyanobacteria of the genus Synechococcus and Synechocystis can produce and release unidentified allelopathic compounds that have both a negative and positive effect on selected cyanobacteria and microalgae.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…These blooms led to the death of bottom flora and benthic fauna and the loss of valuable resources of fish (eel and mullet) and mollusks [62]. Śliwi ńska-Wilczewska et al [57] and Felpeto et al [63] suggest that picocyanobacteria blooms are a new phenomenon that requires comprehensive studies. Although the impacts of climate change on picocyanobacterial blooms are diverse, most current evidence suggests that this process increases the amplitude and frequency of these events [57,64].…”
Section: Discussionmentioning
confidence: 99%